Hydroxyapatite-based coatings on Mg and Ti-based implants: A detailed examination of various coating methodologies - M. Rafiei; H. Eivaz Mohammadloo; M. Khorasani; F. Kargaran; H.A. Khonakdar (Heliyon)
Metallic implants have been considered as promising alternatives to traditional implants due to their biocompatibility and favorable biodegradability properties. However, one of the major challenges in using these implants is the relatively fast degradation rate of metal alloys in the body's electrolyte environment, which can lead to early loss of performance and the release of undesirable degradation products. Applying appropriate coatings with suitable performance on the surface of metal implants can be an effective solution to control the rate of deterioration and increase their stability in the body environment. In this comprehensive study, various methods of coating metal implants with calcium phosphate or hydroxyapatite structures, including sol-gel, chemical deposition (such as hydrothermal deposition), and thermal spraying (such as plasma spray) methods have been fully investigated. The benefits and drawbacks of each of these techniques in relation to the properties of the resulting coating such as surface morphology, chemical composition, adhesion to the substrate, porosity and crystal structure, anti-corrosion performance, their impact on the biological performance of the implant in terms of biocompatibility, degradation rate control, and mechanical properties, as well as limitations related to the coating process are described. The results of this comprehensive study provide valuable and key guidance for choosing the most suitable coating and coating method according to the type of medical application considered for metal implants.